Using near‐infrared reflectance spectroscopy (NIRS) to estimate carbon and nitrogen stable isotope composition in animal tissues - Ancin‐Murguzur, Francisco Javier; Tarroux, Arnaud; Bråthen, Kari Anne; Bustamante, Paco; Descamps, Sébastien (Ecology and evolution, 2021)
Stable isotopes analysis (SIA) of carbon and nitrogen provides valuable information about trophic interactions and animal feeding habits. We used near‐infrared reflectance spectroscopy (NIRS) and support vector machines (SVM) to develop a model for screening isotopic ratios of carbon and nitrogen (δ13C and δ15N) in samples from living animals. We applied this method on dried blood samples from birds previously analyzed for δ13C and δ15N to test whether NIRS can be applied to accurately estimate isotopic ratios. Our results show a prediction accuracy of NIRS (R2 > 0.65, RMSEP < 0.28) for both δ13C and δ15N, representing a 12% of the measurement range in this study. Our study suggests that NIRS can provide a time‐ and cost‐efficient method to evaluate stable isotope ratios of carbon and nitrogen when substantial differences in δ13C or δ15N are expected, such as when discriminating among different trophic levels in diet. In this article, we study how near infrared reflectance spectroscopy (NIRS) can be used to measure stable isotopes in animal tissues. We used seabird blood in our study and obtained satisfactory results for screening populations and discuss further use of NIRS in other tissues.